giải phương trình `2/(x+1)-x/(x-2)=(7x-11)/((x-2)(x+1))`

Question

giải phương trình
`2/(x+1)-x/(x-2)=(7x-11)/((x-2)(x+1))`

in progress 0
Amara 3 tháng 2021-09-15T16:08:32+00:00 2 Answers 10 views 0

Answers ( )

    0
    2021-09-15T16:09:43+00:00

    ` ĐKXĐ: x ne -1 ; 2 `

    ` \frac{2}{x + 1} – \frac{x}{x – 2} = \frac{7x – 11}{(x – 2)(x + 1)} `

    ` <=> \frac{2(x – 2) – x(x + 1)}{(x – 2)(x + 1)} = \frac{7x – 11}{(x – 2)(x + 1)} `

    ` <=> 2x – 4 – x^2 – x – 7x + 11 = 0 `

    ` <=> -x^2 – 6x + 7 = 0 `

    ` <=> -x^2 + x – 7x + 7 = 0 `

    ` <=> -x(x – 1) – 7(x – 1) = 0 `

    ` <=> (x – 1)(-x-7) = 0 `

    ` <=> ` \(\left[ \begin{array}{l}x-1=0\\-x-7=0\end{array} \right.\) 

    ` <=> ` \(\left[ \begin{array}{l}x=1(TMĐK)\\x=-7(TMĐK)\end{array} \right.\) 

    Vậy tập nghiệm phương trình trên là: ` S = {1;-7} `

    0
    2021-09-15T16:10:31+00:00

    $\text{Đáp án + Giải thích các bước giải:}$

    `(2)/(x+1)-(x)/(x-2)=(7x-11)/((x-2)(x+1))` `(ĐKXĐ:x\ne{2;-1})`

    `<=>(2(x-2))/((x+1)(x-2))-(x(x+1))/((x-2)(x+1))=(7x-11)/((x-2)(x+1))`

    `=>2(x-2)-x(x+1)=7x-11`

    `<=>2x-4-x^{2}-x-7x+11=0`

    `<=>-x^{2}-6x+7=0`

    `<=>(-x^{2}+x)-(7x-7)=0`

    `<=>-x(x-1)-7(x-1)=0`

    `<=>(x-1)(-x-7)=0`

    `<=>` \(\left[ \begin{array}{l}x-1=0\\-x-7=0\end{array} \right.\) 

    `<=>` \(\left[ \begin{array}{l}x=1(TM)\\x=-7(TM)\end{array} \right.\) 

    `\text{Vậy}` `S={1;-7}`

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )